Silencing of FTS increases radiosensitivity by blocking radiation-induced Notch1 activation and spheroid formation in cervical cancer cells - Prabakaran, D.S.; Muthusami, Sridhar; Sivaraman, T.; Yu, Jae-Ran; Park, Woo-Yoon (International journal of biological macromolecules, 2019)
Increasing evidence(s) suggests that cancer stem cells (CSC) in tumours contribute to radio-resistance and recurrence. Notch plays an important role in the maintenance of CSC in many cancers including cervical cancer. Previously, we have reported the role of Fused Toes Homolog (FTS) in conferring radioresistance in cervical cancer cells in vitro and human subjects. The present study investigated the regulatory role of FTS in Notch signaling and maintenance of CSC upon irradiation of cervical cancer cells. The expression of Notch1, 2, 3, cleaved Notch1 and its downstream target Hes1, and spheroid formation was increased by irradiation. Silencing of FTS prevented the radiation-induced increase in the expression of Notch signaling molecules and spheroid formation. Immunoprecipitation showed FTS binds Notch1 and Hes1. Also in silico structural analysis identified putative residues responsible for the binding between FTS and Notch1. Spheroid formation and the expression of CSC markers, Nanog, Oct4A and Sox2 were greatly reduced by combining silencing of FTS and radiation. Taken together, these results suggest that FTS is involved in the regulation of irradiation-induced Notch signaling and CSC activation and can be used as a target to increase radiosensitivity in cervical cancer.